PENGEMBANGAN POP-UP MODULE MATERI SISTEM PENCERNAAN MAKANAN PADA MANUSIA KELAS VIII SMP - Sri Hayati; Kurnia Ningsih; Yokhebed Yokhebed (FKIP Universitas Tanjungpura, 2020)
This study aimed to develop pop-up module related to human digestive system of class VIII SMPN 3 Sungai Raya, and to discover students’ responses to the developed module. The Research and Development (R&D) method was conducted comprised 5 stages such as research and data collection, planning, product draft development, limited product testing, and the revision to the operational product. The product was evaluated by 2 validators to measure it’s feasibility by testing the contents, language, course, and graphic aspects. The test was employed to determine the students’ responses in the cognitive, affective, and conative aspects. The subjects in this study are the 8th-grade students of SMPN 3 Sungai Raya with 12 preliminary field test students. The validation of each showed a value of 1.00 with a high category. Limited trials showed that the averages of cognitive, affective, and conative dimensions were respectively 94,72%, 92,01%, 89,58% and the average of the students’ responses were 92,10%, categorized very strong. Therefore, the Pop-up module is feasible for teaching material and the response given by the student’s is positive.